The noise produced by the air handling units depending on the type of engine - Jachimowicz, Sebastian; Gładyszewska-Fiedoruk, Katarzyna (International Conference “Environmental Engineering”, 2017)
The elaboration is the study is to examine the difference in the sound level in the air handling units made by the same producer. These units are of the same design parameters and components, and supply air and exhaust air. The only difference is mounted engines. Tested air handling units are equipped with an engine type EC, and traditional direct drive, controlled by an converter. Sound level measurements were carried out in the ducts supply air ventilation system at a distance of 1 m from the air handling unit and for the unit at a distance of 2 m from the inspection door of the fan section of the supply, with 3 settings efficiency of units 30%, 60% and 90%. Tested headquarters are located inside the building. Excessive noise has a negative effect on the human body, resulting in fatigue, difficulty in learning and concentration, impaired orientation, annoyance, increase in blood pressure, headaches, dizziness, and in the worst case of temporary or permanent hearing loss. For this reason it is very important to protect against noise. Therefore, it was these studies.